2014
DOI: 10.5539/jas.v6n12p152
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Statistical Analysis of the UV-Vis Profiles of Wine Polyphenolic Extracts during Vinification

Abstract: Multivariate Statistical data Analysis (MVA) was used to study the changes undergone by the UV-Vis spectral profiles of polyphenolic components during vinification. Two Sardinian wines, from the white cultivar "Vermentino" and from the red "Cannonau", were studied. The wine samples were collected at different times from the fermentation vessels and the UV-Vis spectra of their solid phase extracts (SPE) were submitted to PCA (Principal Component Analysis) and to Orthogonal Projections to Latent Structures (OPLS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Spectroscopic methods, like Ultraviolet-to-Visible spectroscopy (UV-Vis) [61][62][63][64], Fourier Transformed Infrared spectroscopy (FTIR) [48,[65][66][67][68][69][70][71] are also applied due to their easiness of use, cost-effective and no sample preparation also in combination with numerical/statistical methods (e.g., chemometric methods) [48,66,68,[72][73][74][75].…”
Section: Methods For Characterization Of Must and Winementioning
confidence: 99%
“…Spectroscopic methods, like Ultraviolet-to-Visible spectroscopy (UV-Vis) [61][62][63][64], Fourier Transformed Infrared spectroscopy (FTIR) [48,[65][66][67][68][69][70][71] are also applied due to their easiness of use, cost-effective and no sample preparation also in combination with numerical/statistical methods (e.g., chemometric methods) [48,66,68,[72][73][74][75].…”
Section: Methods For Characterization Of Must and Winementioning
confidence: 99%
“…Conjugation lowers the energy required for electron transitions to take place between OH-phenolic groups, causing an increase of absorption wavelengths in the UV-Vis spectra and subsequent displays of colour (Vallverdú-Queralt et al 2016, Waterhouse et al 2016b. As such, the visible colour of a compound is influenced by its degree of conjugation, with less conjugation causing a material to absorb light at shorter wavelengths (perceived as yellow and red hues) and greater conjugation causing absorption at longer wavelengths (perceived as blue and green hues) (Sanna et al 2014). Experiments have shown that tannins display yellow hues (Amendola et al 2010, Burtch et al 2017, pyranoanthocyanins express red-orange and red-brown hues (Figure 7), copigmentation reactions generate red and brown colours (Amendola et al 2010, Escribano-Bailón et al 2019, Morata et al 2019 and ethyl-linked pigments generate purple colours (Lee et al 2004b).…”
Section: Phenolic Compounds and Wine Colourmentioning
confidence: 99%
“…red anthocyanins or yellow flavonols). The UV-visible spectra of a wine is thus attributed to the electronic transitions occurring within the hydroxyl groups of the phenolic molecules, with different transitions corresponding to the different phenolic subclasses [12]. A number of UV-visible applications have been exploited to quantify phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%